Biodiversity and ecosystem services on the African continent – What is changing, and what are our options? - (:unkn) unknown (My University, 2021)
Throughout the world, biodiversity and nature's contributions to people are under threat, with clear changes evident. Biodiversity and ecosystem services have particular value in Africa– yet they are negatively impacted by a range of drivers, including land use and climate change. In this communication, we show evidence of changing biodiversity and ecosystem services in Africa, as well as the current most significant drivers of change. We then consider five plausible futures for the African continent, each underlain by differing assumptions. In three out of the five futures under consideration, negative impacts on biodiversity and ecosystem services are likely to persist. Those two plausible futures prioritizing environment and sustainability, however, are shown as the most likely paths to achieving long term development objectives without compromising the continent's biodiversity and ecosystem services. Such a finding shows clearly that achievement of such objectives cannot be separated from full recognition of the value of such services.
Keywords: African Research